2015
DOI: 10.21825/scad.v6i1.1136
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface morphology and its correlation with friction performance of brake pads

Abstract: Abstract:The present work presents the morphology evolution of a brake material surface submitted to braking tests through a laboratory-scale tribometer. Optical microscope images of the material's surface were obtained for every 10 braking operations. These images were post-processed in appropriate computational software. By means of the image segmentation technique, morphological parameters related to the brake material surface were estimated. The wear rate and also the coefficient of friction resulting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The above is possible, bearing in mind that the irregularities can be several tens of microtones, and particles are deposited there, which are later released. 15,134,150,151 According to Hagino et al, 34 Figure 3. Influence of sliding speed on brake wear and particle formation.…”
Section: Influence Of Deceleration On the Wear Process And Particle Formation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The above is possible, bearing in mind that the irregularities can be several tens of microtones, and particles are deposited there, which are later released. 15,134,150,151 According to Hagino et al, 34 Figure 3. Influence of sliding speed on brake wear and particle formation.…”
Section: Influence Of Deceleration On the Wear Process And Particle Formation Processmentioning
confidence: 99%
“…The above is possible, bearing in mind that the irregularities can be several tens of microtones, and particles are deposited there, which are later released. 15,134,150,151 According to Hagino et al, 34 drum brakes are more environmentally friendly, bearing in mind that particles collect in the drum and are not released into the atmosphere. When it comes to disc and drum brakes according to Laguna-Camacho et al, 152 it was found that the wear mechanism differs in both types of brakes.…”
Section: Influential Factors On the Wear Process Of Friction Pairs And The Particle Formation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…A bedding-in, also known as running-in, is characterized by a transitory increase in the friction magnitude when the sample wears out locally to conform to the disc surface [15,19]. So, in a bedding-in section is possible to evaluate how long this transitory period lasts.…”
Section: Setup Of the Experimentsmentioning
confidence: 99%
“…The surface characteristic parameters obtained by this method are obviously limited by the resolution and sampling length of the instrument, and do not have objective uniqueness, so it is difficult to fully reflect the random behavior and detailed characteristics of rough surfaces, giving rise to many inconveniences in practical application [4]. In the early days, research on surface structure was limited to surface roughness, which was used to study the relationship between the surface morphology and the contact performance of parts in order to provide accurate quantitative descriptions of surface structures [5]. Since the appearance of the first surface morphology measuring instrument in the 1920s, a great deal of quantitative research on the evaluation parameters of surface morphologies has been undertaken [6].…”
Section: Introductionmentioning
confidence: 99%